The potential for induction of the expression of bone morphogenetic protein-7 and alkaline phosphatase in postextraction tooth sockets using a combination of mangosteen peel extract and DFDBBX - Utari Kresnoadi, Diva Amelia Ruslianda, Harry Laksono (Journal of Applied Pharmaceutical Science, 2022)
This study was determined to verify that the combination of DFDBBX and mangosteen peel extract can increase the expression of bone morphogenetic protein-7 (BMP-7) and alkaline phosphatase (ALP) in tooth sockets on days 7 and 30 after extraction. The central lower incisors of Cavia cobaya were extracted using a needle holder, after which polyethylene glycol (PEG), DFDBBX + PEG, mangosteen peel extract + PEG, and a combination of DFDBBX + mangosteen peel extract + PEG were applied to the tooth socket. On days 7 and 30, the C. cobaya were sacrificed, their lower jaws were soaked in ethylenediaminetetraacetic acid and block paraffin, and a slide was made. Finally, an immunohistochemical examination of the expression of B MP-7 and ALP was performed. Statistical analysis by means of the analysis of variance indicated that each group was significantly different. The combination group showed the highest expression of BMP-7 and ALP on days 7 and 30, followed by the mangosteen peel extract group. A combination of DFDBBX and mangosteen peel extract 2% was applied to the C. cobaya tooth socket after extraction which increased the expression of BMP-7 and ALP on days 7 and 30.
Keywords: DFDBBX, Garcinia mangostana, BMP-7, ALP, medicine